2017
DOI: 10.5505/tjtes.2017.57142
|View full text |Cite
|
Sign up to set email alerts
|

Management of capitellum fractures by open reduction and internal fixation using Herbert screws

Abstract: BACKGROUND: Capitellar fractures are rare elbow injuries and can cause severe limitation of function if not properly managed. Numerous treatments have evolved, from closed reduction and cast immobilization to open reduction and internal fixation (ORIF), so as to achieve a stable joint that allows early mobilization. We determined the functional outcomes of treating these fractures with ORIF using Herbert screws via an extensile lateral approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 23 publications
(56 reference statements)
1
9
0
Order By: Relevance
“…On the other hand, some authors did not observe any AVN in their patients. [13,15,[20][21][22][23] In our study, AVN developed in three patients (14%). This result is consistent with the current literature.…”
Section: Discussionsupporting
confidence: 48%
See 4 more Smart Citations
“…On the other hand, some authors did not observe any AVN in their patients. [13,15,[20][21][22][23] In our study, AVN developed in three patients (14%). This result is consistent with the current literature.…”
Section: Discussionsupporting
confidence: 48%
“…Due to the chondral damage during this injury, these patients are at risk of developing secondary elbow osteoarthrosis. [5,10] In terms of degenerative joint disease or arthrosis, Mighell et al [12] reported arthrosis in 28% of their patients, while Sultan et al [13] observed arthrosis only in one patient (7%) from a series of 15 patients who had type I and type IV fractures, according to Bryan and Morrey. All patients in Mahirogullari et al's [15] series had type I fractures, and the authors did not encounter arthrosis in any of their patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations